Interictal discharges delay target‐directed eye movements and impair attentional set‐shifting in children with epilepsy. Issue 10 (24th July 2022) - Warsi, Nebras M.; Wong, Simeon M.; Suresh, Hrishikesh; Arski, Olivia N.; Yan, Han; Ebden, Mark; Kerr, Elizabeth; Smith, Mary Lou; Ochi, Ayako; Otsubo, Hiroshi; Sharma, Roy; Jain, Puneet; et al.
Abstract: Objective: The theory of transient cognitive impairment in epilepsy posits that lapses in attention result from ephemeral disruption of attentional circuitry by interictal events. Eye movements are intimately associated with human attention and can be monitored in real time using eye‐tracking technologies. Here, we sought to characterize the associations between interictal epileptiform discharges (IEDs), gaze, and attentional behavior in children with epilepsy. Methods: Eleven consecutive children undergoing invasive monitoring with stereotactic electrodes for localization‐related epilepsy performed an attentional set‐shifting task while tandem intracranial electroencephalographic signals and eye‐tracking data were recorded. Using an established algorithm, IEDs were detected across all intracranial electrodes on a trial‐by‐trial basis. Hierarchical mixed‐effects modeling was performed to delineate associations between trial reaction time (RT), eye movements, and IEDs. Results: Hierarchical mixed‐effects modeling revealed that both the presence of an IED ( β  ± SE = 72.74 ± 24.21 ms, p  = .003) and the frequency of epileptiform events ( β  ± SE = 67.54 ± 17.30 ms, p  < .001) were associated with prolonged RT on the attentional set‐shifting task. IED occurrence at the time of stimulus presentation was associated with delays in gaze initiation toward the visual targets ( p  = .017). Significance: The occurrence of epileptiform activity in close temporal association with stimulus presentation is associated with delays in target‐directed gaze and prolonged response time, hallmarks of momentary lapses in attention. These findings provide novel insights into the mechanisms of transient impairments in children and support the use of visual tracking as a correlate of higher order attentional behavior.